The Effect of The Combination Juice of Guava and Red Spinach on The Hemoglobin Level of Pregnant Women on Third Trimester in Health Center of Melak - Susanti, Indah; Kalsum, Umi; Siregar, Nursyahid (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Indonesia is a developing country that has a very high prevalence of anemia in pregnancy. The results of the Riskesdas data show that pregnant women experiencing anemia in Indonesia increased from 37.1% to 48.9%. Anemic pregnant women have difficulty, and bleeding during childbirth. Meanwhile, babies are at risk of being born LBW. Objective: The purpose of this study was to determine the effect of giving a combination of red guava juice and red spinach on the Hb levels of pregnant women in the third trimester in the working area of the Melak Health Center. Methods: This study uses a quantitative approach, quasi experiment with Non-Equivalent Control Group Design. Resultand Discussion: The results showed that there were differences in the Hb levels of respondents between the intervention and control groups after being given the research intervention (p-value = 0,000).  There was a difference in Hb levels of pregnant women in the third trimester in the intervention group between before and after being given the research intervention. Conclusion: It is expected that pregnant women can increase the intake of vegetables that are high in iron and vitamin C such as guava and red spinach, as an effort to prevent and overcome anemia in pregnancy